A Comparative Study of ARIMA, Artificial Neural Networks, and Kalman Filter Models for Dhaka Stock Exchange Forecasting - Biva, Anika Tahsin; Khan, Md Shafiul Alom; Hossain, A B M Shahadat (GANIT: Journal of Bangladesh Mathematical Society, 2024)
Abstract not available GANITJ. Bangladesh Math. Soc. 44.1 (2024) 29-58